2009
DOI: 10.1016/j.bbadis.2008.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Viral parkinsonism

Abstract: Parkinson's disease is a debilitating neurological disorder characterized that affects 1-2% of the adult population over 55 years of age. For the vast majority of cases, the etiology of this disorder is unknown, although it is generally accepted that there is a genetic susceptibility to any number of environmental agents. One such agent may be viruses. It has been shown that numerous viruses can enter the nervous system, i.e. they are neurotropic, and induce a number of encephalopathies. One of the secondary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
280
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(288 citation statements)
references
References 164 publications
3
280
1
2
Order By: Relevance
“…PEP shares cardinal symptomatology with idiopathic PD including rigidity and bradykinesia but a lack of Lewy body formation (Jang et al, 2009a). Moreover, Takahashi et al, 1995 demonstrated that the H1N1 virus preferentially targets the SNpc, the primary site of pathology in PD (Takahashi et al, 1995).…”
Section: Epidemiological Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…PEP shares cardinal symptomatology with idiopathic PD including rigidity and bradykinesia but a lack of Lewy body formation (Jang et al, 2009a). Moreover, Takahashi et al, 1995 demonstrated that the H1N1 virus preferentially targets the SNpc, the primary site of pathology in PD (Takahashi et al, 1995).…”
Section: Epidemiological Evidencementioning
confidence: 99%
“…This emerging "two-hit hypothesis" in the aetiology of neurodegenerative diseases such as PD, suggests that the disease is multifactorial, and possibly a consequence of "multiple-hits" involving a variety of inflammatory stimuli (Di Monte, 2003). Infectious agents may comprise the first "hit", therefore sensitising the brain to subsequent "hits", which may not have been pathogenic in the absence of an already "primed" system (Jang et al, 2009a). In this instance, microglia in the aged or diseased brain are said to be "primed"…”
Section: Systemic Inflammation and Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, oxidative stress preferentially affects DA neurons in the SNpc, which are particularly vulnerable as they operate under high oxidant conditions due to reduced levels of the anti-oxidant glutathione (Misra & Kalita, 2010;Sian et al, 1994). Accordingly, it has been postulated that pre-exposure to environmental toxins such as heavy metals, organophosphate compounds, neurotoxins, and pesticides like paraquat and rotenone which can induce oxidative stress and the generation of free radicals, increases the susceptibility to the development of PD in later life (Calne & Langston, 1983;Jang et al, 2009a). Pathological and clinical evidence has also identified the involvement of the gastrointestinal tract in enhancing susceptibility to idiopathic Parkinsonism, with Helicobacter pylori infection proposed as a potential trigger in disease progression (Tansey & Goldberg, 2010;Weller et al, 2005).…”
Section: Systemic Inflammation and Parkinson's Diseasementioning
confidence: 99%
“…Postulated risk factors implicated in idiopathic PD include age, genetic predisposition, bacterial or viral infections, neuronal injury such as traumatic brain injury or stroke, and environmental toxins (Koprich et al, 2008;Tansey & Goldberg, 2010). Associations were first established towards the end of the first world war when the H1N1 influenza-A pandemic was coupled with a dramatic increase in post-encephalitic Parkinsonism (PEP) (also referred to as "sleeping sickness" or von Economo encephalitis) (Jang et al, 2009a;Rail et al, 1981;Tansey et al, 2007). People born during this time were at a 2-3 fold increased risk of developing PD, with PEP implicated in 50% of all Parkinsonism cases (Jang et al, 2009a;Tansey et al, 2007).…”
Section: Systemic Inflammation and Parkinson's Diseasementioning
confidence: 99%